Optimal portfolio allocation between global stock indexes and safe haven assets: Gold versus the Swiss Franc : 1999-2021 - Marco Tronzano (Journal of Risk and Financial Management, 2022)
This paper contributes to the literature on safe haven assets, analyzing gold and the Swiss Franc's defensive properties inside various global stocks portfolios. The analysis relies on monthly data extending over the last two decades. Drawing on Multivariate Garch DCC models, the hedging effectiveness of bivariate Swiss Franc-hedged portfolios is found to be notably higher than that of gold-hedged portfolios. Value-at-Risk simulations, assuming equal or "optimal" portfolio weights, confirm these results inside a multivariate asset framework, while a regression approach with quantile dummies provides further support in this regard. Since the better hedge and safe haven properties of the Swiss Franc are likely to persist in the future, the main policy implication of the paper concerns asset allocation strategies giving relatively more weight to the Swiss currency in global stock portfolios.
Keywords: 650; gold; hedging effectiveness; optimal asset allocation; safe haven assets; stock prices; Swiss Franc